Penerapan Model Maturitas Digital Pada Kinerja Startup - Putri, Novianti Indah; Iswanto; Dwijayanti, Andina; Komalasari, Rita; Munawar, Zen (TEMATIK, 2022)
This study aims to apply a digital maturity model to measure startup performance. The maturity model consists of dimensions and criteria, which describe the area of ​​action, and maturity stages which indicate the evolutionary path to maturity. Data collection was obtained using a questionnaire given online at the startup. The research design consisted of three steps: developing a digital maturity model dimension through literature review, expert interviews, and focus groups, online surveys among individuals, and data analysis using the Rasch algorithm and cluster analysis. From these findings, it can be said that some attention should be paid to the business intelligence capacity of startups, given its impact on company performance. In addition, the effect of network learning through business intelligence is significant and presents a positive influence on performance. The results from empirical studies show that understanding the strategic importance of digitalization, as well as using digital technology for collaboration, is already practiced in most companies. However, creating a personalized customer experience based on big data analysis or process automation is characterized by a lower level of achievement. Companies are starting to carry out digital transformation more systematically and strategically, by creating measurable goals and defining roles and responsibilities within the organization. These results help practitioners as well as researchers, better understand the processes through which organizations are truly involved in their digital transformation.